THE ANALYSIS OF THE POSTGRADUATE THESES WRITTEN ON THE FIELD OF RECREATION IN TURKEY FROM 1980 TO 2018 - AYAR, Harun; KOÇ, Mustafa Can (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2018)
This study was carried out with the aim of providing an insight to individuals and future studies in this field by observing how much increase from the beginning of the dissertations about recreation in our Turkey. During this study, electronic archive system of the council of higher education was observed to find the dissertations on recreation in Turkey between the years of 1980- 2018. As a result of the researches, we discovered 402 studies which are 321 of post graduate and 81 of doctorate dissertations. Key words of recreation, spare time, leisure time were searched in the search part of electronic archive system of the council of higher education to get the dissertations in the field of recreation. Dissertations on recreation were evaluated by considering their years, universities, topics, main topics, institutions, access situations, title of consultant and total pages. While these data were getting, we paid attention the studies which have the same words with others. Thus, it has been avoided to use them twice. SPSS 24 was used for data collection. At the first phase of the analysis, general situation; distribution by years, universities, topics and main topics of the post graduate dissertations were examined. In conclusion, recreation has been gathered around 12 different main themes and 34 different department has carried out dissertation around these themes. This has revealed that recreation is a multidimensional department and a lot of fields effect recreation. If the dissertations or articles about recreation not only focus on this field but also other fields and common studies are carried out as far as possible, recreation will be understood better and it will make significant contributions to the field.